(untitled) (Journal of Mathematical Study, 2021)
In this paper, the following p(x)-Laplacian equation: Δ_p(x)u+V(x)|u|^p(x)-2u=Q(x)f(x,u), x∈R^N, is studied. By applying an extension of Clark's theorem, the existence of infinitely many solutions as well as the structure of the set of critical points near the origin are obtained.